2016
DOI: 10.1371/journal.pone.0158455
|View full text |Cite
|
Sign up to set email alerts
|

Development of Kinematic Graphs of Median Nerve during Active Finger Motion: Implications of Smartphone Use

Abstract: BackgroundCertain hand activities cause deformation and displacement of the median nerve at the carpal tunnel due to the gliding motion of tendons surrounding it. As smartphone usage escalates, this raises the public’s concern whether hand activities while using smartphones can lead to median nerve problems.ObjectiveThe aims of this study were to 1) develop kinematic graphs and 2) investigate the associated deformation and rotational information of median nerve in the carpal tunnel during hand activities.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 36 publications
1
30
0
11
Order By: Relevance
“…Smartphones and tablet computers involve thumb or finger interactions with the screen. Although these activities are generally not physically rigorous, prolonged periods of repetitive motion could lead to excessive force being exerted on the median nerve, thereby compressing it . A recent study found that, on average, students use electronic devices over 3 h per day and report musculoskeletal complaints.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Smartphones and tablet computers involve thumb or finger interactions with the screen. Although these activities are generally not physically rigorous, prolonged periods of repetitive motion could lead to excessive force being exerted on the median nerve, thereby compressing it . A recent study found that, on average, students use electronic devices over 3 h per day and report musculoskeletal complaints.…”
mentioning
confidence: 99%
“…Although these activities are generally not physically rigorous, prolonged periods of repetitive motion could lead to excessive force being exerted on the median nerve, thereby compressing it. 2 A recent study found that, on average, students use electronic devices over 3 h per day 3 and report musculoskeletal complaints. In addition, use of electronic devices compels users to engage in extension/flexion and radial/ulnar deviation of the wrist.…”
mentioning
confidence: 99%
“…An ultrasound transducer was placed transversely at the level of carpal tunnel the ultrasound transducer was carefully held without applying any pressure on the participant's skin, and was maintained at an angle perpendicular to the median nerve. Median nerve CSA was determined by performing a boundary trace along the border between the hypoechoic inner median nerve and the hyperechoic outer epineurium [13] .…”
Section: Methodsmentioning
confidence: 99%
“…All participants were requested to sit on a chair facing the examiner with shoulder slightly abducted, the elbow of dominant hand flexed approximately at 90, forearm rested on the table in partially supinated (approximately 45º) to enable them to assume a posture generally applied when using a smartphone for text messaging. During the ultrasound examination, participants were instructed to move their thumb and keep other parts of the hand still when writing on smartphone [13,14] .…”
Section: Measurementsmentioning
confidence: 99%
“…The current study findings are consistent with Inal et al 19 who found that Visual Analogue Scale (VAS) pain in movement was also found to be significantly higher in the high smartphone-user group than in the lower smartphone-user group. In 2006, Woo et al found that ulnar and radial deviations are negatively affected by the prolonged usage of smartphones 20 . They have reported that the gradual reduction in the cross sectional area of the median nerve, with thumb opposition together with the wrist in ulnar deviation, cause the greatest extent of deformation of the median nerve.…”
Section: Measurementmentioning
confidence: 99%